2022
DOI: 10.3390/ijms23148018
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Activation of a Specific Type-5 Metabotropic Glutamate Receptor Antagonist in the Ventrobasal Thalamus Causes Analgesia in a Mouse Model of Breakthrough Cancer Pain

Abstract: Breakthrough cancer pain (BTcP) refers to a sudden and transient exacerbation of pain, which develops in patients treated with opioid analgesics. Fast-onset analgesia is required for the treatment of BTcP. Light-activated drugs offer a novel potential strategy for the rapid control of pain without the typical adverse effects of systemic analgesic drugs. mGlu5 metabotropic glutamate receptor antagonists display potent analgesic activity, and light-induced activation of one of these compounds (JF-NP-26) in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The aim of this study was to determine the region-specific behavioral and electrophysiological effects of mGlu5 receptor blockade with caged and photoswitchable NAMs in neuropathic pain using photopharmacology. While the effect of optical manipulations of photosensitive mGlu5 NAMs in individual brain regions in pain models has been studied before ( 12, 13, 32 ), the comparative analysis across different brain regions and their contribution to systemically applied NAMs represents a novel concept.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this study was to determine the region-specific behavioral and electrophysiological effects of mGlu5 receptor blockade with caged and photoswitchable NAMs in neuropathic pain using photopharmacology. While the effect of optical manipulations of photosensitive mGlu5 NAMs in individual brain regions in pain models has been studied before ( 12, 13, 32 ), the comparative analysis across different brain regions and their contribution to systemically applied NAMs represents a novel concept.…”
Section: Resultsmentioning
confidence: 99%
“…Photopharmacological approaches have recently been explored for pain modulation by members of our team (12)(13)(14) and by others (15,16). The drug treatment of neuropathic pain, i.e., chronic pain originating from damage or disease of the somatosensory system, remains a major therapeutic challenge and unmet medical need because of severe side effects and a high percentage of patients resistant to medication (17,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breakthrough pain is frequent in cancer patients and is often characterized by a rapid onset, short duration, and severe intensity ( 5 , 40 ). In this study, the prevalence of breakthrough cancer pain was 41.5% and it was consistent with previous studies that reported 39.3% ( 41 ), 41% ( 42 ), and 40.3% ( 43 ).…”
Section: Discussionmentioning
confidence: 99%